2021
DOI: 10.3390/cancers13215387
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy in Medulloblastoma: Current State of Research, Challenges, and Future Perspectives

Abstract: Medulloblastoma (MB), a primary tumor of the central nervous system, is among the most prevalent pediatric neoplasms. The median age of diagnosis is six. Conventional therapies include surgical resection of the tumor with subsequent radiation and chemotherapy. However, these therapies often cause severe brain damage, and still, approximately 75% of pediatric patients relapse within a few years. Because the conventional therapies cause such severe damage, especially in the pediatric developing brain, there is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 140 publications
(171 reference statements)
0
11
0
Order By: Relevance
“…The challenge has always been overcoming the intricate system of barriers that complicates delivery and efficacy [ 102 ]. However, several immunotherapeutic approaches have reached clinical trials for MB, particularly immune checkpoint inhibitors that target the immunosuppressive brain tumor microenvironment [ 103 ]. To date, the most notable examples of effective immune checkpoint inhibitors are antibodies against cytotoxic-T-lymphocyte antigen 4 (CTLA-4) and the programmed cell death protein (PD-1) and its ligand PD-L1.…”
Section: Group 3 Medulloblastomamentioning
confidence: 99%
“…The challenge has always been overcoming the intricate system of barriers that complicates delivery and efficacy [ 102 ]. However, several immunotherapeutic approaches have reached clinical trials for MB, particularly immune checkpoint inhibitors that target the immunosuppressive brain tumor microenvironment [ 103 ]. To date, the most notable examples of effective immune checkpoint inhibitors are antibodies against cytotoxic-T-lymphocyte antigen 4 (CTLA-4) and the programmed cell death protein (PD-1) and its ligand PD-L1.…”
Section: Group 3 Medulloblastomamentioning
confidence: 99%
“…Cancer immunotherapy using immune checkpoint (IC) blockade has shown promising results in treating solid tumors ( 7 , 8 ). Currently, PD-1, PD-L1, and CTLA4 are the best-established targets, already having FDA-approved monoclonal antibodies for the treatment of many different cancer types ( 9 ; 10 ). However, applying a single immune checkpoint blocker for these targets in CNS tumors, particularly medulloblastoma, did not attain the expected results in clinical trials, particularly in pediatric patients ( 11 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the knowledge of the non-canonic checkpoints is still poorly described in medulloblastoma and could represent new promising targets for therapy ( 9 , 17 ). Hence, the immune checkpoint expression profile characterization in medulloblastomas is of utmost importance and could provide crucial cues for more effective and appropriate immune checkpoint blockade-based immunotherapy ( 10 , 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, cancer immunotherapy has made significant progress with the application of immune checkpoint inhibitors (ICs). Cytotoxic T-lymphocyteassociated antigen 4 (CTLA-4), programmed death 1 (PD-1), and programmed cell death 1 ligand 1 (PD-L1) inhibitors had shown good safety and efficacy in various tumor types, including genitourinary oncology, gastrointestinal oncology, and hematologic tumor (1). It is reported that high mutational burden and PD-L1 expression of urothelial carcinoma made it more sensitive to immunotherapy (2,3), and several ICs had been approved to treat it (4).…”
Section: Introductionmentioning
confidence: 99%